Thermomechanical coupling in glassy polymers: An effective temperature theory - Xiao, Rui; Tian, Chuanshuai; Xu, Yangguang; Steinmann, Paul (International Journal of Plasticity, 2022)
Glassy polymers exhibit a strong thermomechanical coupling when subjected to mechanical loading. A homogeneous strain distribution can be achieved in uniaxial compression conditions. However, a clear temperature increase is observed when the loading rate is relatively high, which further results in a decrease in stress due to thermal softening. In tensile tests, necking instability can easily occur. A temperature change is accompanied by the nucleation and propagation of necked regions. In this work, we apply the effective temperature theory, which can capture the nonequilibrium structure evolution of amorphous polymers, to investigate the thermomechanical behavior of glassy polymers. We demonstrate that a finite element model based on the effective temperature theory can well capture the stress response and the temper-ature increase of polycarbonate (PC) compressed at different loading rates. We further combine experiments and simulations to investigate the effects of the loading rate and aging treatment on the necking behavior in amorphous glassy polymer poly(ethylene terephthalate)-glycol (PETG) in uniaxial tension loading tests. Through employing digital image correlation and infrared thermometry, the strain distribution and the temperature field can be fully characterized during the formation and propagation of necked regions. The model captures all important features of localization behavior observed in experiments, including the force-displacement relationship, and the strain and temperature distribution with necking propagation. However, it underestimates the maximum strain and temperature when the displacement is large. Both experimental and simulative results indicate that increasing loading rate and aging time can induce an increase of the intrinsic strain softening due to a more active structural state caused by mechanical rejuvenation. This further leads to more pronounced localized behavior and a ductile-brittle transition. Our work proves that the effective temperature model is a powerful theoretical framework to predict the complex thermomechanical response of glassy polymers.
CRIS-Team WoS Importer:2022-07-29